CO2 Electroreduction in Organic Aprotic Solvents: A Mini Review - Оrest Kuntyi; Galyna Zozulya; Mariana Shepida (Journal of Chemistry)
An annual increase of CO2 concentrations in the atmosphere causes global environmental problems, addressed by systematic research to develop effective technologies for capturing and utilizing carbon dioxide. Electrochemical catalytic reduction is one of the effective directions of CO2 conversion into valuable chemicals and fuels. The electrochemical conversion of CO2 at catalytically active electrodes in aqueous solutions is the most studied. However, the problems of low selectivity for target products and hydrogen evolution are unresolved. Literature sources on CO2 reduction at catalytically active cathodes in nonaqueous mediums, particularly in organic aprotic solvents, are analyzed in this article. Two directions of cathodic reduction of CO2 are considered—nonaqueous organic aprotic solvents and organic aprotic solvents containing water. The current interpretation of the cathodic conversion mechanism of carbon (IV) oxide into CO and organic products and the main factors influencing the rate of CO2 reduction, Faradaic efficiency of conversion products, and the ratio of direct cathodic reduction of CO2 are given. The influence of the nature of organic aprotic solvent is analyzed, including the topography of the catalytically active cathode, values of cathode potential, and temperature. Emphasis is placed on the role of water impurities in reducing CO2 electroreduction overpotentials and the formation of new CO2 conversion products, including formate and H2.